Soil Spectral Behavior Related to Its Load-Bearing Capacity Based on Moisture Content - Ahmed Elawad Eltayeb Ahmed; Alaa El Hariri; Péter Kiss (Applied Sciences, 2023)
Soil’s load-bearing capacity is a crucial property from which the ability of soil to resist the vertical deformation resulting from a normal load can be determined, and this property is essential for analyzing a vehicle’s performance over soil terrain in terramechanics studies. Soil’s moisture content has a significant impact on its load-bearing capacity and spectral behavior. This study aims to show the relation between the load-bearing capacity and the spectral behavior of sandy loam soil. The study presents the load-bearing capacity and color results of sandy loam soil at different moisture contents. The load-bearing capacity was measured using the Bevameter technique, and the color was measured using spectrophotometer technology that sends waves in the visible range (400–700 nm). The pressure–sinkage results of the tested soil show that with an increase in the moisture content, the bearing capacity of the soil decreases, and the color results show a decrease in the color reflectance with the increase in the moisture content. The measurements were performed in the laboratory of the vehicle technology department at Hungarian University of Agriculture and Life Sciences (MATE).